The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41419-017-0227-9
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning, induced by sub-toxic dose of the neurotoxin L-BMAA, delays ALS progression in mice and prevents Na+/Ca2+ exchanger 3 downregulation

Abstract: Preconditioning (PC) is a phenomenon wherein a mild insult induces resistance to a later, severe injury. Although PC has been extensively studied in several neurological disorders, no studies have been performed in amyotrophic lateral sclerosis (ALS). Here we hypothesize that a sub-toxic acute exposure to the cycad neurotoxin beta-methylamino-L-alanine (L-BMAA) is able to delay ALS progression in SOD1 G93A mice and that NCX3, a membrane transporter able to handle the deregulation of ionic homeostasis occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 40 publications
(49 reference statements)
2
24
0
Order By: Relevance
“…In particular, for the first time, we observed that Nurr1 is physiologically expressed in the Furthermore, since neuroinflammation is a characteristic hallmark of ALS (see Fig.S1 and S2, in agreement with Ilieva et al, 2009;Boido et al, 2014;Anzilotti et al, 2018) and, in addition, Nurr1 is reported to play an anti-inflammatory role in astrocytes and microglial cells (Saijo et al, 2009), we investigated its expression respectively in GFAP-and CD68-positive cells.…”
Section: Sod1-g93a Micesupporting
confidence: 57%
“…In particular, for the first time, we observed that Nurr1 is physiologically expressed in the Furthermore, since neuroinflammation is a characteristic hallmark of ALS (see Fig.S1 and S2, in agreement with Ilieva et al, 2009;Boido et al, 2014;Anzilotti et al, 2018) and, in addition, Nurr1 is reported to play an anti-inflammatory role in astrocytes and microglial cells (Saijo et al, 2009), we investigated its expression respectively in GFAP-and CD68-positive cells.…”
Section: Sod1-g93a Micesupporting
confidence: 57%
“…A recent study reported that an injection of a sub-toxic dose of BMAA into the cerebrospinal fluid delayed the progression of ALS in an ALS mouse model, which was suggested to have occurred due to prevention of the down-regulation of Na + /Ca 2+ exchanger 3 (NCX3) 42 . NCX3 has been reported to be involved in cell cycle progression 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the entry of Ca 2+ into the mitochondria contributes to establish the chronic depolarization of the mitochondrial membrane, which consequently determines the release of pro-apoptotic proteins and the activation of enzymes able to activate other cell death pathways (Jaiswal, 2013 ). Hereupon, we documented the importance of the plasmamembrane Na + /Ca 2+ exchanger isoform 3 (NCX3) in ALS pathogenesis because animals affected by ALS show a strong reduction in its expression and activity at muscular and neuronal levels, whereas strategies able to delay ALS progression worked also through NCX3 activation and overexpression (Anzilotti et al, 2018 ). NCX, by contributing to the maintenance of Na + and Ca 2+ homeostasis, takes part to the progression of some neurological diseases including stroke, seizure, multiple sclerosis and Alzheimer Disease (Annunziato et al, 2004 , 2007 , 2013 ; Sirabella et al, 2009 ; Molinaro et al, 2011 , 2013 ; Pannaccione et al, 2012 ; Lanzillotta et al, 2013 ).…”
Section: Role Of Calcium (Ca 2+ ) Ionsmentioning
confidence: 99%
“…NCX, by contributing to the maintenance of Na + and Ca 2+ homeostasis, takes part to the progression of some neurological diseases including stroke, seizure, multiple sclerosis and Alzheimer Disease (Annunziato et al, 2004 , 2007 , 2013 ; Sirabella et al, 2009 ; Molinaro et al, 2011 , 2013 ; Pannaccione et al, 2012 ; Lanzillotta et al, 2013 ). Up to now, within the CNS, three different isoforms, NCX1, NCX2 and, NCX3, and numerous splicing variants have been identified; the precise involvement of each NCX isoform in ALS progression and etiology has not yet been determined, nonetheless some seminal works postulated a crucial role for NCX3 in mediating the impairment in neuromuscular transmission occurring ALS and in other related disease (Sokolow et al, 2004 ; Boscia et al, 2012 ; Casamassa et al, 2016 ; Anzilotti et al, 2018 ), thus rendering it a putative druggable target in ALS. On the other hand, as previously mentioned, In familiar ALS, mitochondrial Ca 2+ overload, caused by Cu/Zn-superoxide dismutase 1 (SOD1) mutation, causes strong ROS generation.…”
Section: Role Of Calcium (Ca 2+ ) Ionsmentioning
confidence: 99%
See 1 more Smart Citation